Educational Programs of Universal Design for Preparation and Training of Personnel - Yu. Mamedova, I.; ., . (International Journal of Engineering and Technology, 2018)
The training of engineering and design personnel capable of taking into account the principles of universal design in their work will allow creating comfortable living conditions not only for people with disabilities in health, but also for certain categories of citizens by taking into account the needs.Â Â